The CTRP3-AdipoR2 Axis Regulates the Development of Experimental Autoimmune Encephalomyelitis by Suppressing Th17 Cell Differentiation - Murayama, Masanori A.; Chi, Hsi-Hua; Matsuoka, Mako; Ono, Takahiro; Iwakura, Yoichiro (Frontiers in Immunology, 2021)
C1q/TNF-related proteins (CTRP) including CTRP3 are a group of secreted proteins which have a complement C1q-like domain in common, and play versatile roles in lipid metabolism, inflammation, tumor metastasis and bone metabolism. Previously, we showed that the expression of C1qtnf3, encoding CTRP3, is highly augmented in joints of autoimmune arthritis models and CTRP3-deficiency exacerbates collagen-induced arthritis in mice. However, the mechanisms how CTRP3-deficiency exacerbates arthritis still remain to be elucidated. In this study, we showed that CTRP3 was highly expressed in Th17 cell, a key player for the development of autoimmune diseases, and Th17 cell differentiation was augmented in C1qtnf3–/– mice. Th17 cell differentiation, but not Th1 cell differentiation, was suppressed by CTRP3 and this suppression was abolished by the treatment with a receptor antagonist against AdipoR2, but not AdipoR1, associated with suppression of Rorc and Stat3 expression. Furthermore, AdipoR1 and AdipoR2 agonist, AdipoRon suppressed Th17 cell differentiation via AdipoR2, but not AdipoR1. The development of myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis was enhanced in C1qtnf3–/– mice associated with increase of Th17 cell population. CTRP3 inhibited MOG-induced IL-17 production from T cells by affecting both T cells and dendritic cells. These results show that CTRP3 is an endogenous regulator of Th17 differentiation, suggesting that the CTRP3-AdipoR2 axis is a good target for the treatment of Th17 cell-mediated diseases.